Review of Sentiment Analysis and Opinion Mining Algorithms - Can, Ümit; Alataş, Bilal (Munzur Üniversitesi, 2017)
Sentiment Analysis or Opinion Mining is an important field in text mining.  Nowadays the products which are produced by companies or persons are reached to consumers mercurially and reviews about these products issued on web pages. As understood easily these reviews are very significant for producers. In addition to that, Sentiment Analysis can be used from financial field to medicine field. Sentiment Analysis investigates a text that has a positive, negative or a neutral meaning. In general, we can imagine Sentiment Analysis as the computational treatment of opinions, sentiments, and subjectivity of text. In this study, a research about Sentiment Analysis has been performed and Sentiment Analysis classification techniques have been explained with its all parts.  Many articles related with Sentiment Analysis have been studied and briefly explained. Then, one application about Sentiment Analysis has been shown for understanding more about Sentiment Analysis. Consequently, a general assessment of this issue has been done and the study has been finished with the result section.

Duygu Analizi veya Fikir Madenciliği, metin madenciliğinin önemli bir alanı ve son yılların önemli araştırma konularından biridir. Günümüzde şirketlerin veya kişilerin ürettikleri ürünler çok hızlı bir şekilde tüketiciye ulaşmakta ve bu ürünlerle ilgili yapılan yorumlarda gelişen teknoloji ile beraber internet dünyasına yansımaktadır. Bu yorumların ne anlama geldiği üreticiler için çok önemlidir. Bunun dışında Duygu Analizi veya Fikir Madenciliği finanstan tutun da tıp alanına kadar birçok alanda kullanılabilir. Duygu Analizi; bir metni ele alarak bu metnin olumlu, olumsuz veya tarafsız bir içeriğe sahip olup olmadığını inceler. Genel olarak fikirlerin, duyguların ve metinlerin nesnelliğinin hesaplanma işlemi de denilebilir. Bu çalışma da, Duygu Analizi hakkında araştırma yapılmış olup Duygu Analizi sınıflandırma teknikleri incelenerek tüm alt bileşenleri ile beraber anlatılmıştır. Duygu Analizi ile ilgili birçok güncel makale incelenmiş ve kısaca anlatılmıştır. En son olarak genel bir değerlendirme ve sonuç yazılarak çalışma bitirilmiştir.
Duygu Analizi ve Fikir Madenciliği Algoritmalarının İncelenmesi
Keywords: Engineering; Mühendislik